The Mayeigh Nozeigh Tradition as A Means of Transmitting Islamic Educational Values in The Padang Sawah Community, Kampar: A Study of The Living Qur’an-Hadith: Tradisi Mayeigh Nozeigh sebagai Sarana Penanaman Nilai-Nilai Pendidikan Islam di Masyarakat Padang Sawah, Kampar: Sebuah Studi living Al-Qur’an dan Hadis - Zikri Darussamin (Takwil: Journal of Quran and Hadith Studies, 2026)
The Mayeigh Nozeigh tradition is a religious cultural practice of the community in Padang Sawah Village, Kampar Kiri Subdistrict, Kampar Regency, carried out as a way to fulfill a vow and express gratitude to Allah SWT for the fulfillment of their hopes. This tradition serves as a customary ritual and acts as a medium for transmitting Islamic educational values, as well as a representation of the practice of the “living Qur’an” and “living hadith” in community life. This study aims to analyze the Mayeigh Nozeigh tradition as a means of transmitting Islamic values and to examine the community’s reception of the Qur’an and hadith, which form its foundation. The study employs a qualitative approach using ethnographic methods, including observation, in-depth interviews, and documentation. The results indicate that this tradition embodies the values of tawhid, gratitude, responsibility in fulfilling vows, charity, ukhuwah, mutual cooperation, and social bonding. These values stem from the community’s understanding of Qur’anic verses and hadiths regarding the obligation to fulfill vows, express gratitude, share, and strengthen social bonds. Religious texts are accepted as guidelines for life, interpreted as the religious foundation of the tradition, and actualized through communal prayers, vow feasts, food charity, and collective community participation. The transmission process occurs through the exemplary conduct of religious and traditional leaders, oral transmission, and community involvement in the practice of these traditions. These findings indicate that Mayeigh Nozeigh serves as a space for the reproduction of Islamic values as well as a manifestation of the “living Qur’an” and “living hadith” within the Kampar Malay community.